2021
DOI: 10.33448/rsd-v10i2.12819
|View full text |Cite
|
Sign up to set email alerts
|

Resistance mechanisms of Cryptococcus spp. and plant compounds as tools to combat them

Abstract: Cryptococcus is a genus of dimorphic basidiomycete fungi found in the form of yeasts and filaments. Cryptococcosis has as main etiological agents the species Cryptococcus neoformans and Cryptococcus gattii. This disease is considered a public health problem and has becoming more alarming because of the limitations of antimicrobials available to its treatment, in addition to an increase in reports of fungal resistance. In this sense, the present review sought to survey information on the resistance mechanisms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 146 publications
0
3
0
Order By: Relevance
“…The structures of several common metabolites are presented in Figure 3 . Mechanisms involved in antifungal resistance include enzymatic drug inactivation, expression of efflux pumps and drug transporters, modifications in the drug target, alternative metabolic pathways and biofilm formation ( Karpiński et al, 2021 ; Silva et al, 2021 ). As one of the most prevalent fungal pathogens causing fungal diseases in humans, the resistance of Candida albicans to antifungals is of concern.…”
Section: Plants With Antimicrobial Activity and Their Mechanisms Of A...mentioning
confidence: 99%
See 2 more Smart Citations
“…The structures of several common metabolites are presented in Figure 3 . Mechanisms involved in antifungal resistance include enzymatic drug inactivation, expression of efflux pumps and drug transporters, modifications in the drug target, alternative metabolic pathways and biofilm formation ( Karpiński et al, 2021 ; Silva et al, 2021 ). As one of the most prevalent fungal pathogens causing fungal diseases in humans, the resistance of Candida albicans to antifungals is of concern.…”
Section: Plants With Antimicrobial Activity and Their Mechanisms Of A...mentioning
confidence: 99%
“…The high fungistatic activity demonstrated by the sterol alkaloid tomatidine may be due to its involvement in the ergosterol pathway as shown by the upregulation of ergosterol genes in tomatidine-treated C. albicans ( Dorsaz et al, 2017 ). Numerous studies have reported anti-cryptococcal activities of plant extracts and essential oils which may be attributed to the induction of fungal morphological changes, ergosterol synthesis inhibition, cell division interruption, reduced activity of enzymes such as laccase and urease as well as inhibition of biofilm formation ( Silva et al, 2021 ). Besides, biofilm production may inhibit the activity of antifungals and contribute to drug tolerance or resistance.…”
Section: Plants With Antimicrobial Activity and Their Mechanisms Of A...mentioning
confidence: 99%
See 1 more Smart Citation